일본 의료소년원의 현황과 평가 - 강경래; Kang Kyung-rea (소년보호연구, 2014)
The purposes of this study are to review Treatment provided in a Japanese medical reformatory. The following four types of Japan juvenile training schools are used to accommodate juveniles according to their age, level of criminal tendency, and physical and mental condition, etc. at the time of their admission: (1)Primary juvenile training schools:Juveniles generally aged 12 or older but typically younger than 16 and without any serious physical/mental disabilities; (2)Middle juvenile training schools:Juveniles generally aged 16 or older but younger than 20 and without any serious physical/mental disabilities; (3)Special juvenile training schools:Juveniles generally aged 16 or older but younger than 23 and without any serious physical/mental disabilities but with strong criminal tendencies. However, juveniles younger than 16 sentenced to imprisonment can also be accommodated here; and (4)Medical juvenile training schools: Juveniles generally aged 12 or older but younger than 26 and with serious physical/mental disabilities. Treatment courses are established with both general short-term treatment program and long-term treatment program (with further divisions of the treatment courses also being available within the long-term treatment program). All the juveniles in juvenile training schools are provided with guidance in five areas of correctional education, namely daily life guidance, vocational guidance, academic education, health and physical education, and special activities. However, they categorize each juvenile to one of the treatment courses each of which is set with different weight of priority on each of these five areas of correctional education, according to the criminal tendency, academic ability, future plans, and physical and mental condition of each juvenile to implement the treatment in the manner most effective (medical treatment has priority in the medical treatment course). The treatment course also notes the key matters that require attention in the course of implementing the correctional education.